Cross cultural validation of the Minimal Assessment of Cognitive Function in Multiple Sclerosis (MACFIMS) and the Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) - Dusankova, Jana Blahova; Kalincik, Tomas; Havrdova, Eva; Benedict, Ralph H B (The Clinical neuropsychologist, 2012)
The available instruments for cognitive assessment in multiple sclerosis (MS) require considerable time and resources, and are not readily available in all countries. The study aimed to examine validity of the Czech translation of the Minimal Assessment of Cognitive Function in MS (MACFIMS), to validate the Brief International Cognitive Assessment for MS (BICAMS), and to compare their outcomes. We evaluated 367 MS patients and 134 healthy controls with the MACFIMS battery, which comprises the three tests of the BICAMS (Symbol Digit Modalities Test, Brief Visuospatial Memory Test-Revised, California Verbal Learning Test, second edition). The most accurate BICAMS criterion of cognitive deficit was that of at least one of the overall three tests outside the normal range (sensitivity = 94%, specificity = 86%, p = 10(-28)). Outcomes of the Czech translation of the MACFIMS were comparable to its original. The MACFIMS and the BICAMS identified cognitive deficit in 55% and 58% of the MS patients, respectively. Both batteries predicted patient self-reported vocational status. This is the first study to show that the BICAMS is highly sensitive and specific to cognitive impairment in MS as defined by the MACFIMS. This impairment is associated with vocational status. Czech versions of the studied batteries have now been validated.
Keywords: referenční hodnoty; Sensitivity and Specificity; senzitivita a specificita; Humans; neuropsychologické testy; Multiple Sclerosis; Female; Cross-Cultural Comparison; dospělí; srovnání kultur; lidé; Employment; reprodukovatelnost výsledků; Adult; Cognition Disorders; Neuropsychological Tests; ženské pohlaví; roztroušená skleróza; Male; Reproducibility of Results; zaměstnanost; Czech Republic; Reference Values; kognitivní poruchy; Česká republika; mužské pohlaví